The Effectiveness of Arbitration as an Alternative Dispute Resolution in the Indonesian Legal System - Muhammad yunus; Ahmad Farhan Jumain; Muhammad Zaitun; Mutiara El Rahmah (ISNU Nine-Star Multidisciplinary Journal, 2024)
Arbitration has become an important alternative in dispute resolution in Indonesia, regulated by Law No. 30/1999 on Arbitration and Alternative Dispute Resolution. This article aims to analyze the effectiveness of arbitration in the context of the Indonesian legal system, identify its advantages and challenges, and compare it with other dispute resolution methods. This research uses a qualitative method with a literature study approach to extract data from various legal sources and arbitration practices. The results show that arbitration offers a number of advantages, including speed, more efficient costs, and confidentiality. However, there are significant challenges such as a lack of public understanding of arbitration, sometimes high costs, and variability in the quality of arbitrators. In the context of the case studies, there is concrete evidence supporting the effectiveness of arbitration, although enforcement of international arbitral awards still faces obstacles in domestic courts. In comparison with litigation and mediation, arbitration shows higher efficiency, but still requires improvement in the aspects of quality and enforcement of awards. This article recommends increasing public education, adjusting fees, strengthening the quality of arbitrators, and improving enforcement of awards to increase the effectiveness of arbitration in Indonesia. Thus, arbitration can contribute more significantly to the legal system and investment climate in Indonesia.